Detection of Salmonella in food samples by the combination of immunomagnetic separation and PCR assay - Jeníková, G; Pazlarová, J; Demnerová, K (International microbiology, 2000)
A combination of immunomagnetic separation and polymerase chain reaction (IMS-PCR) was used to detect Salmonella in food samples. Pre-enrichment of samples was combined with filtration through a membrane for the removal of food debris. The IMS-PCR assay combines selective extraction of bacteria by specific antibodies with primer specific PCR amplification that enables to detect Salmonella in non-fatty food samples in 24 h. In comparison with conventional cultural methods, the IMS-PCR is a rapid and specific method. Combined with filtration bags, it partially reduces the negative effects of the food matrix and allows the quick detection of Salmonella cells. The shortened protocols for Salmonella spp. detection described here can improve considerably current methodologies.